Prospective associations between parental feeding practices and children's oral processing behaviours. Issue 1 (27th July 2018) - Fogel, Anna; Fries, Lisa R.; McCrickerd, Keri; Goh, Ai Ting; Chan, Mei Jun; Toh, Jia Ying; Chong, Yap‐Seng; Tan, Kok Hian; Yap, Fabian; Shek, Lynette P.; Meaney, Michael J.; Broekman, Birit F.P.; et al.
Abstract: Previous research demonstrated that faster eating rates are linked with increased intake of energy during a meal. Here, we examined whether within‐meal parental feeding practices show cross‐sectional and prospective associations with children's oral processing behaviours and whether the previously demonstrated association between faster eating rates and higher energy intakes varies by parental feeding practices. A subset ( n = 155) of children and their mothers from the Growing Up in Singapore Towards healthy Outcomes cohort participated in an ad libitum meal at age 4.5 years. Children's oral processing behaviours (eating rate, bite size, chews per gram, oral exposure time, and meal duration) and parental feeding practices (autonomy‐supporting and coercive prompts, restrictions, hurrying, and slowing) were recorded during the meal. Subsequently, 94 of the children participated in a follow‐up meal without their mothers at age 6 years. Parental feeding practices were not consistently associated with child oral processing behaviours overall. However, exploratory post hoc analyses revealed some sex differences. The mothers of girls with faster eating rates, larger bite sizes, and fewer chews were more likely to use hurrying, slowing, and restrictions, but similar associations were not observed among boys. Children who had the most problematic eating style and were eating fast and for long experienced more restrictions, instructions to slow down, and prompts. Faster eating rates were linked with the highest energy intakes if children were additionally prompted to eat. Prospective analyses showed that children who were more often prompted using coercive techniques and less frequently hurried at age 4.5 years had faster eating rates at 6 years and a larger increase in eating rates between ages 4.5 and 6 years but did not consume more energy. Although the direction of these associations cannot be assumed, these exploratory analyses suggest sex differences in the associations between feeding practices and oral processing behaviours and highlight the potential role of parents in the development of children's oral processing behaviours.